The Prevalence and Outcome of Teenage Pregnancies in a Tertiary Care Teaching Hospital: Prevalensi dan Luaran Kehamilan Remaja pada Rumah Sakit Pendidikan Tersier - I Putu G Kayika; Farrah Lidyasna (Indonesian Socety of Obstetrics and Gynecology, 2018)
Abstract Objectives: To examine the prevalence as well as maternal and perinatal outcome of teenage pregnancies. Methods: For analyzing the prevalence of the teenage mothers, we used cross-sectional study design by evaluating the medical records of all pregnant mothers who went to the obstetric clinic of Cipto Mangunkusumo Hospital, Jakarta, Indonesia, during January 2014 until December 2016. For the outcome of the teenage mothers, we used retrospective study design by analyzing medical records of teenage mothers who had delivery at the delivery ward of Cipto Mangunkusumo Hospital during January 2014 until December 2016. We compared their outcomes to outcomes of pregnant women aged 20 to 30 years old delivered at the same hospital in the same period. Maternal outcomes that were measured include preeclampsia, methods of delivery, anemia, and postpartum hemorrhage, as well as perinatal outcomes including preterm delivery, and low birthweight. Results: Among 3.578 outpatients at Obstetric Clinic, RSUPN Cipto Mangunkusumo, we got 503 pregnant subjects, 16 (3.2%) were teenagers. Among 520 subjects who had delivery, 78 (15%) subjects were â‰¤ 19 years old. Teenage pregnancy was significantly associated with anemia (p < 0.05, adjusted OR = 2,08) and low birthweight (p < 0.05, adjusted OR = 1.83). Teenage pregnancy was not significantly associated with preeclampsia, methods of delivery, postpartum hemorrhage, and preterm delivery. Conclusion: The prevalence of teenage pregnancy at Cipto Mangunkusumo Hospital is 3.2% and teenage mothers who had delivery is 15%. Teenage mothers are at increased risk of anemia and delivering low birth weight babies. Keywords: maternal outcome, perinatal outcome, prevalence,teenage pregnancies Abstrak Tujuan: Penelitian ini bertujuan untuk mengetahui prevalensi kehamilan remaja serta luarannya. Metode: Untuk menganalisis prevalensi ibu remaja, kami menggunakan desain studi potong lintang dengan mengeavaluasi rekam medis dari seluruh ibu hamil yang berobat ke klinik obstetri RSUPN Cipto Mangunkusumo pada periode Januari 2014 sampai Desember 2016. Pada luaran ibu hamil, kami menggunakan desain studi retrospektif dengan menganalisis rekam medis ibu remaja yang bersalin di RSUPN Cipto Mangunkusumo pada periode yang sama. Luaran ibu remaja dibandingkan dengan ibu yang bersalin yang berusia 20-30 tahun. Luaran ibu yang kami ukur meliputi preeklampsia, metode persalinan, anemia, perdarahan pasca persalinan, sedangkan luaran perinatal yang kami ukur meliputi kelahiran prematur dan BBLR. Hasil: Dari seluruh 3.578 pasien di Poliklinik Obstetri RSUPN Dr. Cipto Mangunkusumo, diperoleh 503 subjek yang hamil,sebanyak 16 (3.2%) subjek adalah remaja. Dari seluruh 520 subjek yang bersalin, 78 (15%) subjek adalah remaja. Kehamilan remaja berhubungan signifikan dengan anemia (p < 0.05, adjusted OR = 2.08) dam BBLR (p < 0.05, adjusted OR = 1.83). Kehamilan remaja tidak berhubungan signifikan dengan preeklamsia, metode persalinan, perdarahan pascapersalinan, dan kelahiran prematur. Kesimpulan: Prevalensi kehamilan remaja di RSUPN Dr. Cipto Mangunkusumo adalah 3.2% dan persalinan remaja di RSUPN Dr. Cipto Mangunkusumo adalah 15%. Ibu remaja berada pada peningkatan risiko anemia dan melahirkan bayi BBLR. Kata kunci: kehamilan remaja, luaran ibu, luaran perinatal, prevalensi,